Role of microbial and phytoplanktonic communities in the control of seawater viscosity off West Antarctica (30-80°W). - Seuront, Laurent; Leterme, Sc; Seymour, Js; Mitchell, Jg.; Ashcroft, D.; Noble, W.; Thompson, Pg; Davidson, At; Van Den Enden, R.; Scott, Fj; Wright, Sw; Chapperon, C.; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2010)
International audience Despitethelong-standingbeliefthatseawaterviscosityisdrivenbytemperatureandsalinity, biologicallyincreasedseawaterviscosityhasrepeatedlybeenreportedinrelationtophytoplankton exudatesinshallow,productivecoastalwaters.Here,seawaterviscositywasinvestigatedinrelationto microbialandphytoplanktoniccommunitiesoffthecoastofEastAntarcticaalonglatitudinaltransects located between301E and801E insub-surfacewatersandatthedeepchlorophyllmaximum(DCM).The physicalcomponentofseawaterviscosityobservedalongeachtransectsrangedfrom1.80to1.95cP, while theactualseawaterviscosityrangedfrom1.85to3.69cP.Thisresultedinbiologicallyincreased seawaterviscosityreachingupto84.9%insub-surfacewatersand77.6%attheDCM.Significantpositive correlationswerefoundbetweenelevatedseawaterviscosityand(i)bacterialabundanceinsub-surface watersand(ii)chlorophyll a concentrationandtheabundanceofflowcytometrically-definedauto-and heterotrophicprotistsattheDCM.Amongthe12groupsand108speciesofprotistsidentifiedunder light microscopy,dinoflagellatesandmorespecifically Alexandriumtamarense and Prorocentrum sp. were themaincontributorstothepatternsobservedforelevatedseawaterviscosity.Ourobservations, which generalisedthelinkpreviouslyidentifiedbetweenseawaterviscosityandphytoplankton compositionandstandingstocktotheSouthernOcean,arethefirstdemonstrationofincreasesin seawaterviscositylinkedtomarinebacterialcommunities,andsuggestthatthemicrobially-increased viscositymightquantitativelybeatleastasimportantastheonerelatedtophytoplanktonsecretion. & 2009 ElsevierLtd.Allrightsreserved